THEORETICAL ASPECTS OF PROFESSIONAL SELF-DEVELOPMENT OF FUTURE FOREIGN LANGUAGE TEACHERS (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical foundations of professional self-development of future foreign language teachers, the practical methodological system, tools and technological foundations of professional self-development of future foreign language teachers, the effectiveness of professional self-development of future foreign language teachers. Also, the theoretical aspects of professional self-development of future foreign language teachers are analyzed.